Threshold Dynamics in a Periodic Three-Patch Rift Valley Fever Virus Transmission Model. (9th January 2019) - Wen, Buyu; Teng, Zhidong; Liu, Wenlin
Abstract : This paper investigates a three-patch Rift Valley fever virus transmission model with periodic coefficients. The basic reproduction numberR i 0 i = 1, 2, 3 is calculated for the model by using the next infection operator method. The threshold conditions on the extinction and permanence in the mean of the disease with probability one. The Rift Valley fever disease will be permanent in thej -thj = 1, 2, 3 patch ifj ≥ i, R i 0 > 1 and dies out in thej -th patch ifj < i . The numerical simulations are given to confirm the theoretical results.